Effects of a Class-Wide Positive Peer Reporting Intervention on Middle School Student Behavior. (August 2020) - Chaffee, Ruth K.; Briesch, Amy M.; Volpe, Robert J.; Johnson, Austin H.; Dudley, Laura
Class-wide behavioral interventions are a feasible and effective method to support the behavior of all students. In six peer-reviewed studies, Tootling, a class-wide intervention that combines positive peer reporting with an interdependent group contingency, has increased positive peer reports and academically engaged behavior (AEB), and decreased disruptive behavior (DB). However, no prior studies have been conducted with middle school students, and none have employed strategies to promote enduring behavior change. A withdrawal design with maintenance phase, implemented across two middle school classrooms, found moderate effects (nonoverlap of all pairs [NAP] = 0.74, Tau-U = −0.48) of Tootling on decreasing DB and moderate to large effects (NAP = 0.76, Tau-U = 0.68) on increasing AEB, although internal threats to validity prevented the demonstration of a clear functional relationship across both classrooms. Results from the maintenance phase, in which the group contingency reward was removed, suggest promising strategies to support durable behavioral change. Limitations of the present study, directions for future research, social validity, and implications for practice are discussed.